252 Impact of Pre- and Postnatal Nutritional Extremes on Tonic Secretion of Gonadotropins and Feedback Responsiveness to Estradiol in Sexually Mature Heifers. (8th October 2021) - Garza, Viviana; Kellerman, Julie I; Maia, Tatiane S; Cardoso, Rodolfo C; Williams, Gary L
Abstract: Objectives were to test the hypotheses that nutritional extremes during prenatal development interact with postnatal nutrition during the juvenile period of heifers to impact 1) tonic secretion of gonadotropins, and 2) estradiol-17β (E2) negative and positive feedback responsiveness in adulthood. Heifers were selected from a larger population programmed nutritionally using a 3 x 2 factorial arrangement of pre- and postnatal diets. Beginning at 90 days of pregnancy, Bos indicus-influenced cows (n = 95) were fed to achieve body condition scores (BCS; 1–9 scale) of 3–3.5 (L; thin), 5.5–6 (M; moderate), or 7.5–8 (H; obese) by onset of the third trimester and maintained thereafter. Heifer offspring were weaned at 3–3.5 months of age and assigned to either a low- (L; 0.5 kg/day) or high-gain (H; 1.0 kg/day) diet until 8 mo. of age, then fed a common diet until puberty. Heifers (n = 18; 6/grp) representing HH, MH and LL combinations were ovariectomized postpubertally (17.1 mo. of age) and received E2 replacement. In Exp. 1, blood samples were collected at 10-min intervals to evaluate pulsatile secretion of LH and FSH for 5.5 hours. In Exp. 2, heifers received E2 (2.4 ug/kg I.M.), with blood sampling at 30-min to 1-h intervals for 30 h. Heifers in the MH (1.25 ± 0.11 ng/mL) group tended (P < 0.09) to have greater LH pulse amplitude compared to HH (0.91 ± 0.14 ng/mL) and LL (0.96 ± 0.09 ng/mL); otherwise, frequency, amplitude, and mean concentrations of LH and FSH did not differ among groups. Exogenous E2 (Exp. 2) suppressed (P < 0.0001) mean plasma concentrations of LH and FSH equally among groups, then stimulated equivalent surges of LH beginning at 14 ± 0.02 h, with only two FSH surges detected. Neither pre- nor postnatal nutrition affected E2 negative or positive feedback in this study.